Real-world data on the Immunity Response to the COVID-19 Vaccine among Patients with Central Nervous System Immunological Diseases: Immune Response to COVID-19 Vaccine in CNS Immunological Disease - Kosiyakul, Punchika; Jitprapaikulsan , Jiraporn; Uawithya, Ekdanai; Wongprompitak , Patimaporn; Chaimayo, Chutikarn; Horthongkham , Navin; Angkasekwinai , Nasikarn; Tisavipat, Nanthaya; Prayoonwiwat , Naraporn; Rattanathamsakul, Natthapon; Boonyapisit , Kanokwan; Kumutpongpanich , Theerawat; et al. (Siriraj Medical Journal, 2024)
Objective: The effects of immunotherapies on the immune response to various regimens of SARS-CoV-2 vaccines in patients with autoimmune neurological disease have been demonstrated in limited data. Thus, we evaluated the immune responses in each platform of COVID-19 vaccination between patients with autoimmune neurological disease and a healthy population. Materials and Methods: We conducted a prospective observational study. We collected serum from patients with autoimmune neurological diseases to perform serological methods using anti-RBD IgG assay, neutralizing antibodies assay, and interferon SARS-CoV-2 immunoassay. Serological response level was analyzed by platforms of vaccines and types of immune modifying therapy. Results: Fifty-eight patients had tested for an anti-RBD IgG response, and those receiving no immunotherapy/ healthy controls had the highest median anti-RBD IgG levels amongst immunotherapy statuses. Rituximab in those who received inactivated or mRNA vaccine regimens had the lowest antibody level compared with other immunotherapies. In vector-based vaccine regimens, significant reductions of anti-RBD IgG response were observed in all other immunotherapy groups except for azathioprine, with the greatest difference seen compared to rituximab. Thirty-five patients with positive anti-RBD responses were further tested for neutralizing antibodies. The mRNA vaccine regimen demonstrated the highest inhibition percentage among the Delta and Omicron variants. Twentytwo patients were tested for T cell responses, with no significant difference in T-cell activity across all groups. Conclusion: We have demonstrated a significant decrease in antibody response against SARS-CoV-2 in patients with autoimmune neurological diseases receiving immunotherapies compared to a healthy population, especially for patients taking rituximab.